Pengaruh Keaktifan Belajar Terhadap Hasil Belajar Siswa Madrasah Tsanawiyah - Nadia Wulidar Rohmah; Didit Hermawan (Universitas Maritim AMNI Semarang, 2025)
This literature study examines the effect of learning activeness on learning outcomes in various Madrasah Tsanawiyah in Indonesia. In order for student learning outcomes to improve, teachers need to have the ability to develop student learning activeness in every learning process. Efforts to generate student learning activeness are needed so that the implementation of learning activities can run effectively. This study uses a literature review approach by analyzing various related scientific sources. The results showed that student learning activeness affects the improvement of student learning outcomes. Learning activeness has an important role because it can encourage self-confidence and improve student learning outcomes.